Open data framework for MTUN academics using open data license as mediator - Ismael, Siti Nur' Asyiqin (2022)
Data sharing has become prominent nowadays. The need for data sharing in the educational world is crucial and worth exploring as higher education is one of the critical sectors that produce a vast amount of data.However, most of the data are not permitted to be published, always kept in a silo, unavailable and confidential.The hesitation of data sharing are perhaps due to universities’ disinterest to embrace the potential of Open Data and at the same time universities have difficulties in opening up data and identifying workable practices that strike a balance between sharing data while maintaining its privacy and security. Due to these reasons, the Open Data initiatives are introduced to explore and embrace the data potential. In this study, the Technological, Organisational, and Environmental (TOE) framework and Theory of Planned Behaviour (TPB) were integrated to examine the factors influencing data sharing. The intention of data sharing is expected when it comes to Open Data.There were questioned whether the theories and approaches related to the developed, modified, and extended Open Data in the advanced countries are relevant to a developing country such as Malaysia and whether other determinants and mediators play essential roles in the specific environment.Therefore, this study examined the factors that influence Malaysia Technical University Network (MTUN) academics on data sharing and the existence of a mediator between data sharing and Open Data. In seeking empirical evidence of data sharing practices and Open Data, this study undertook a preliminary study to confirm the problem of data sharing and Open Data within the MTUN environment. Seventeen (17) MTUN Officers were interviewed by conducting a Personal Structured Interview.Based on the preliminary study, the concerns of misuse of personal data (29.41%), data integrity (23.53%), data privacy, security (17.65%) and, infringement of data act (17.65%) were highlighted.The development of Open Data Framework for MTUN Academics (OD-MTUN-ACA) was based on the factors that influence MTUN academics on data sharing and the introduction of Open Data Licenses (ODL) as a mediator between Data sharing and Open Data. The quantitative method; survey technique was used in collecting primary data. Samples were selected using stratified random sampling, which yielded 442 usable questionnaires. The result of Confirmatory Factor Analysis (CFA) showed that the factors that influence MTUN academics on data sharing depend on these components; technical infrastructure, usability, norms, data sharing policy, resources, data sharing culture, research practice, attitude, normative belief, and perceived behavioural control.These components met the fitness indexes in CFA analysis and were found to have a significant influence on the data sharing. Structural Equation Modeling (SEM), was used to analyse structural relationships between data sharing, ODL, and Open Data. Based on the analysis, ODL was found significant in mediating the relationship between data sharing and Open Data. This result was once again reconfirmed with the bootstrapping method.The introduction of ODL as a mediator would solves the concerns of misuse of personal data, data integrity, data privacy, security and, infringement of data act. Thus, OD-MTUN-ACA must include ODL as one of the additional components. In general, this study successfully achieved its main objective; the development of OD-MTUN-ACA and the introduction of new mediator, ODL. It was hoped that this study would narrow down the gaps in the knowledge area and could trigger Open Data initiatives among Malaysia Universities.